Geography homeworks - didactic challenges or just learning obligations? - Kolnik, Karmen; Dobnik, Tanja (Journal for Geography, 2014)
In the article there are some theoretical starting points presented as homework being an important part of educational process. Pupils threw homework complement the gained knowledge and are developing abilities at courses, above all they are training their independent learning and recognising personal responsibilities for it. With the case study af the Primary school Petrovče we are introducing the research on frequence, intended use and content of homework at the class of geography and the motivation of pupils and teachers for them. Results are indicating, that pupils, and teachers are on theoretical level otherwise  aware of the positive influence of homework on pupils learning and development of independence. Nevertheless pupils are not regularly doing their homework and teachers are giving too little diverse and differential thought-out homework.